The Effect of Self-Efficacy and Entrepreneurial Knowledge on Entrepreneurial Interest with Motivation as an Intervening - Saryadi Saryadi; Liss Dyah Dewi Arini; Bangun Prajadi Cipto Utomo (Journal of Social Entrepreneurship and Creative Technology, 2024)
Universities have a role in shaping students' specialization in entrepreneurship. The small interest of university alumni needs to be carried out in various studies. Factors that if they are influential need to be studied. The purpose of this study is to determine the direct and indirect influence of self-efficacy, entrepreneurial knowledge on entrepreneurial interest with motivation as an intervening variable.  The number of samples filled out were students of Duta Bangsa University Surakarta in the 3rd semester of the Faculty of Law and Business Management Study Program with 44 respondents, the Faculty of Health Sciences S1 ARS Study Program with 8 respondents and the RMIK Study Program with 53 respondents through google form so that the number of samples was 105. Data analysis through path analysis, data quality test/survival test and statistical test.  The results showed that self-efficacy and entrepreneurial knowledge had a significant positive effect on motivation. Self-efficacy and entrepreneurial knowledge have a significant positive effect on entrepreneurial interest. Motivation has a positive but not significant effect on entrepreneurial interest. The direct influence of self-efficacy is the most effective variable in influencing the interest in self-efficacy.